Physical Design of High-Performance Fuel Assembly Based on Fully Ceramic Microencapsulated Fuel for Supercritical CO2 Cooled Reactor - Di Lu (Frontiers Media S.A., 2021)
Fully ceramic microencapsulated fuel (FCM) is employed in the supercritical CO2 (S-CO2)-cooled reactor as accident tolerant fuel (ATF). Although the fuel and the assembly substrate contain SiC, the assembly cannot be sufficiently moderated due to the weak moderating performance of S-CO2, which affects the neutronics economy seriously. In this study, a new fuel assembly based on FCM fuel is proposed for the S-CO2 cooled reactor. Besides, the solid moderator rod is introduced into the design. Although the introduction of moderator rods can effectively improve the moderation performance of S-CO2 reactor assembly, it will lead to the deterioration of uniform moderation. To further improve the uniform moderation, arrangement of moderator rods and fuel enrichment partition are studied. Finally, the results show clearly that a better balance between uniform moderation and sufficient moderation can be obtained in the high-performance S-CO2 reactor assembly.